Balbuk haus / Muhammad Hanif Danial Basri - Basri, Muhammad Hanif Danial (College of Creative Arts, Universiti Teknologi MARA, Kedah, 2024)
Established in 2019 by Ahmad Soffi Bin Abdul Manah, BALBUK HAUS initially started as a regular café serving traditional cuisine. Over time, it transformed into a unique café oGering a picturesque view due to its strategically located position, drawing visitors seeking a distinctive experience. The cafe's unique selling proposition revolves around the challenge of savoring delicious food while relishing the breathtaking backdrop of the nearby hill. The phrase 'RASA DISEBALIK ANCALA' signifies that the café's allure lies not only in its exceptional menu but in its captivating location, capturing the a ention of a wide audience. The term 'Ancala' within the tagline refers to the ancient Malay word for hill or mountain. My primary focus is on enabling everyone to relish the traditional dishes served by the café, such as porridge, lempeng, and keropok lekor-my top preferences-alongside the changing landscapes throughout the day. These range from the blueness of the morning, the verdant hues at midday, to the crimson beauty during sunset. The decision to rebrand this company stemmed from a lack of awareness about its unique location and the café situated within it. Insufficient social media activity contributed to this obscurity. To address this, a website was developed to showcase the café's ambiance, oGerings, and allow for reservations due to limited seating. Additionally. commercial advertise- ments were strategically placed on TikTok, considering its widespread popularity, to expand outreach and a ract a broader audience. The name "Balbuk Haus" originates from the village of Balbuk, where the café is nestled. "Balbuk" translates to "back of the hill" in the local dialect, while "haus" means thirst. This unique name amalgamates these meanings, symbolizing both the café's geographical location and the essence of yearning or thirst, culminating in the distinctive and meaningful identity of "Balbuk Haus." In conclusion, I chose "Balbuk Haus' for its meaningful name, aiming to evoke the serene sensation I experience-an essence of tranquility that accompanies enjoying food amidst the picturesque landscape behind Chuping Hill. This choice also serves to show-case the allure of remote regions in Malaysia, highlighting their inherent charm and unique appeal, disproving any preconceived notions about their lack of intrigue.